A facile and sensitive tetrabromobisphenol-A sensor based on biomimetic catalysis of a metal–organic framework: PCN-222(Fe). Issue 35 (15th August 2018) - Yu, Guangxia; Song, Xin; Zheng, Shijie; Zhao, Qiang; Yan, Danting; Zhao, Jinshun
Abstract : A facile electrode based on a metal–organic framework (PCN-222(Fe)) and acetylene black was fabricated for sensitive detection of tetrabromobisphenol-A (TBBPA). Abstract : A facile electrode based on a metal–organic framework (PCN-222(Fe)) and acetylene black was fabricated for sensitive detection of tetrabromobisphenol-A (TBBPA). As a heme-like enzyme mimic, PCN-222(Fe) exhibited excellent peroxidase-like catalytic activity, which could enhance the electrocatalytic activity towards the oxidation of TBBPA. In addition, on account of its ultra-high surface area and large pore volume, PCN-222(Fe) could intensively adsorb TBBPA from aqueous solution and improve the sensitivity of the proposed sensor. Under optimized conditions, a linear range of 0.001–1.0 μmol L −1 was obtained for the detection of TBBPA, with a detection limit as low as 0.57 nmol L −1 . Furthermore, the sensor was successfully employed to detect TBBPA in water samples, providing a promising alternative for practical application.